Adsorption of Toxic Metal Ions from Aqueous Solutions by Modified Cellulosic Waste Material - Dixit, Arvind; Tiwari, Anuradha; Kumar Yadav, Sunil; Vijay Shukla, Bhakti (Asian Journal of Chemistry, 2012)
The adsorption of Pb(II), Hg(II) and Ni(II) from aqueous solutions by cellulosic material was studied in a batch adsorption system. Factors influencing Pb(II), Hg(II) and Ni(II) adsorption such as metal ion concentration, pH, contact time and adsorbent dosage were investigated. The adsorption process was relatively fast and equilibrium was established with in 4 h. Maximum adsorption of metal ions and a comparison of the kinetic models on the overall adsorption rate showed that the adsorption system was best described by the pseudo second-order kinetics. The fast kinetics results and high adsorption capacity indicated that date pits fibre can be applied as the selective adsorbent for the treatment of heavy metal ions from aqueous solutions. The adsorption mechanism was suggested to be complexation.